PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LERANING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDNEGERI014 TERATAK BULUH - Lilis Suryani; Hendri Marhadi; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
AbstrakThe study was based on the low learning outcomes Elementary School fourth grade students Teratak Buluh 014. Of the 22 students who achieved KKM only 9 people. The purpose of this research is to improve student learning outcomes Elementary School fourth grade Teratak Buluh 014 with the application of learning models Contextual Teaching and Learning. The results of the activity of the teacher 's first meeting of the first cycle first cycle percentage of 62.50 % with enough categories, increased in the second meeting be categorized either 68.75 %. At the first meeting of the second cycle increased with the percentage of 81.25 % in both categories at once and the second meeting of the second cycle of 87.50 % categorized very well. The results of the first cycle activity students first encounter the first cycle enough percentage of 56.25 % category, increasing the percentage of 75.00 % second meeting either category. At the first meeting of the second cycle increased to 81.25 % categorized very well. At the second meeting of the second cycle increased to 87.50 % categorized very well. Mastery learning students on the basis of scores of students who completed 9 students who did not complete while 13 students , with classical completeness 40.90 % (not finished). At the end of the first cycle of repeat students who complete 15 incomplete whereas 7 students, with classical completeness 68.18 % (not finished). At the end of the second cycle replications increased thoroughness, students who pass the 20 students who did not complete while 2 students, with classical completeness 90.90 % ( complete ). It can be concluded that the application of learning models Contextual Teaching and Learning can improve learning outcomes IPS Elementary School fourth grade students Teratak Buluh 014. Keywords: Contextual Teaching and Learning, The Result Of Social Studies